Approach, understanding, needs and integration of the BIM concept in the Romanian modern society - Radu Muntean; Cristina Chițonu; Dorin Radu; Christiana Cazacu; Teofil Gălățanu (IOP Conference Series: Materials Science and Engineering, 2020)
The aim of this study is to look at the level of knowledge about BIM (Building Information Modelling) in 3 important constructions sectors: higher education institutions (HEI) - companies – public bodies. In reference to the studies and surveys made in Romania by a team from Transilvania University of Brasov, in the frame of an Erasmus+ research project - UrbanBIM, it is reasonable to hypothesize that most of the people surveyed did not understand what BIM really is, and some were unable to identify the differences between BIM and CAD (Computer-aided design). Making population surveys and analysing the data allow for determining the methodologies for future implementation of BIM technologies and improving the educational training. The concept understating shows the preponderance of using BIM technology in the construction sector, developed on extended levels, starting from urban planning, geographic information system (GIS), architecture, engineering and construction (AEC), building management and leading to life cycle analysis (LCA) and energy efficiency (EE).
Keywords: BIM